Evaluating the Effectiveness of the iPusnas in Enhancing Elementary Students' Numeracy Skills - Firdaus, Fery Muhamad; Safitri, Amalia Dyah; Amanah, Dita Noor; Fadhli, Rahmat; Hassan, Nurulhuda Md (Record and Library Journal, 2024)
Background of the study: Integrating digital resources in education is increasingly important for enhancing student learning experiences and outcomes. This study examines the impact of using iPusnas e-books on the numeracy skills of fifth-grade elementary school students. Purpose: The primary aim of this study was to determine the effectiveness of iPusnas e-books in improving the numeracy skills of elementary school students compared to traditional learning methods using textbooks. Method: A quasi-experimental design with a non-equivalent control group was employed. The sample consisted of two fifth-grade classes from SD Muhammadiyah 1 Wonopeti, Yogyakarta, Indonesia. One class served as the experimental group using iPusnas e-books, while the other served as the control group using traditional textbooks. Pre-tests and post-tests were administered to assess numeracy skills. Data were analyzed using T-tests and N-Gain tests. Findings: The results indicated a significant improvement in the numeracy skills of students in the experimental group compared to the control group. iPusnas e-books were more effective than traditional textbooks, as evidenced by higher post-test scores and N-Gain values. Conclusion: The study concludes that iPusnas e-books significantly enhance numeracy skills in fifth-grade students, highlighting the potential of digital learning resources to improve educational outcomes.